An Analysis of Factors Influencing Indonesia’s Leading Agricultural Commodities Export to India - Ibnu Muchtar Rosyidi; Heru Irianto; Sutrisno Hadi Purnomo (Caraka Tani: Journal of Sustainable Agriculture, 2021)
Indonesia's trade balance to India had been decreasing since 2013. That has been affected by the downward trend in agricultural export value of Indonesia. This problem has raised Government’s attention to increase the export performance. This research aimed to analyze the determinants of Indonesia’s leading agricultural commodities export to India. Panel data regression model was explored to analyze secondary data of the range year 2001 to 2017. The factors examined in this study were India’s real Gross Domestic Product (GDP) per capita, Rupiah exchange rate, export price of Indonesia agricultural commodities and India’s import tariff. Model testing used the Chow, Hausman and Lagrange tests to compare and select the best model. The determinant of the variables testing used statistical and classical assumption tests. The results showed that India’s real GDP per capita has positive influence to the export value which means an increase in the purchasing power of trading partners would increase the value of exports. The Rupiah exchange rate has negative influence to the export value which means that the depreciation of rupiah to dollar causes a decrease in the export value. The export price of Indonesia’s agricultural commodities have positive influence on the export value, however the tariff has no effect. The policy that can be suggested to the government is to provide support and encourage domestic producers to increase exports to India.